Self-defensive subjectivity: The diagnosis of a social pathology. (October 2014) - Kautzer, Chad
In his book Das Recht der Freiheit (2011), Axel Honneth develops a theory of social justice that incorporates negative, reflexive and social forms of freedom as well as the institutional conditions necessary for their reproduction. This account enables the identification of social pathologies or systemic normative deficits that frustrate individual efforts to relate their actions reflexively to a normative order and inhibits their ability to recognize the freedom of others as a condition of their own. In this article I utilize Honneth's theory in the diagnosis of a contemporary social pathology, which impedes social recognition and thereby contributes to social injustice. I argue that this particular social pathology – associated with the Second Amendment right to bear arms – has given rise to a pernicious form of subjectivity, which I call self-defensive . I conclude with some remarks concerning what this application reveals about the strengths and weaknesses of Honneth's account.